Review of the genus Meganola Dyar, 1898 of Ivory Coast and adjacent areas with descriptions of 5 new species and several taxonomic updates (Lepidoptera, Nolidae, Nolinae)—Taxonomic studies on West African Nolinae I. - László, Gyula M. (Zootaxa, 2020)
The present paper contains the first comprehensive taxonomic summary of the Meganola Dyar, 1898 species recorded in Ivory Coast and adjacent areas. 35 species are recorded in total with 28 species having been collected on recent African Natural History Research Trust expeditions. All species are listed with label data of specimens examined together with 56 colour and 52 black and white illustrations of the adults and their genitalia. A Lectotype is designated for Meganola furvitincta (Hampson, 1914), five species are described as new to science (Meganola smithi, M. taiana, M. subchionea, M. cinereoparva, M. hackeri spp. n.) and 23 new synonymies are established: Meganola endoscota undosaria Hacker, 2012 syn. n., M. kaduna Hacker, 2012 syn. n., M. mabiriaria Hacker, 2012 syn. n. and M. simplicifacta Hacker, 2012 syn. n. are synonymised with M. endoscota (Hampson, 1914); M. polioleuca Hacker, 2012 syn. n. is synonymised with M. mesonephele (Hampson, 1914); M. togatulella Hacker, 2012 syn. n., M. subterminalis Hacker, 2012 syn. n. and M. lupii Hacker & Hausmann, 2012 syn. n. are synonymised with M. lucia (van Son, 1933); M. septima Hacker, 2012 syn. n., M. octava Hacker, 2012 syn. n., M. heteromorpha Hacker, 2012 syn. n., M. dissoluta Hacker, 2012 syn. n., M. brachyvalva Hacker, 2012 syn. n. and M. pseudofuscata Hacker, 2012 syn. n. are synonymised with M. monofascia (van Son, 1933); M. mbala Hacker, 2014 syn. n. and M. poliographa Hacker, 2012 syn. n. are synonymised with M. furvitincta (Hampson, 1914); M. obscuritata Hacker, 2012 syn. n. is synonymised with M. spermophaga (Fletcher, 1962); M. tabbertiella Hacker & Hoppe, 2012 syn. n., M. amaniella Hacker, 2012 syn. n. and M. fuscostriata Hacker, 2012 syn. n. are synonymised with M. pyrrhomorpha Hacker, 2012; M. longisigna Hacker, 2012 syn. n. and M. politzari Hacker, 2012 syn. n. are synonymised with M. foviferoides (Poole, 1989); Meganola eburneana Hacker, 2012 syn. n. is synonymised with M. illaudata (Fletcher, 1958). The hitherto unknown males of Meganola dananae Hacker, 2012, M. rhyssomorpha Hacker, 2012 and M. mesothermoides (Poole, 1989) as well as females of M. microfascia Hacker, 2012 and M. palaeographa Hacker, 2012 are illustrated for the first time and several new distribution records are provided.